Indonesia (Effect of Phosphate Solubilizing Bacteria and P Fertilizer on Maize Growth (Zea mays L.) on Mature Oil Palm (Elaeis guineensis Jacq.) Stage 1 - Henriawaty, R Dwi Puspita; Suherman VZ, Cucu; Ariyanti, Mira (Jurnal Penelitian Kelapa Sawit, 2024)
Open space at the mature phase of oil palm can be used to increase land productivity through an intercropping pattern with maize. Inceptisol soil has low chemical fertility especially P content, efforts that can be made to increase the P content of soil are by applying biological fertilizers such as phosphate solubilizing bacteria (PSB). This study aimed to determine and examine the effect of PSB and various doses of P fertilizer to increase the growth and yield of maize in mature phase oil palm plantations. The experiment was carried out at the Ciparanje Experimental Garden, Faculty of Agriculture, Padjadjaran University from January to April 2023. The experiment was carried out using a randomized block design (RBD) method consisting of seven treatments and repeated four times. The treatment consisted of 100% dose of SP-36, 50 kg/ha PSB + 25% dose of SP-36, 50 kg/ha PSB + 50% dose of SP-36, 50 kg/ha PSB + 75% dose of SP-36, 75 kg/ha PSB + 25% dose of SP-36, 75 kg/ha PSB + 50% dose of SP-36, 75 kg/ha PSB + 75% dose of SP-36. The results showed that the application of PSB and P fertilizer effected on the plant height, stem diameter, cob length, cob diameter, dry weight of 100 seeds, dry weight per plant, dry weight per plot, and dry weight per hectare. A dose of 50 kg PSB and 25% P fertilizer is the most efficient dose and the use of PSB can reduce the need for P fertilizers by up to 75%.